An Overview of Listed Summer Residences and Villas in Zagreb (Prostor, 2023)
The goal of the research was to establish a complete overview of summer residences, villas and (family) houses in Zagreb, exclusively on the basis of listing criteria. 60 listed buildings were identified, all located in the northern part of Zagreb, on the southern slopes of Medvednica. The paper provides a review of listed building locations, authors, time of construction, historical stylistic classification, analysis of the pertaining listing documentation and literature review. Summer residences for an occasional stay were built during the 18th and 19th century in secluded hilly locations surrounded by vineyards and orchards. In the 20th century, the construction of summer residences decreased, while the construction of villas for permanent residence begins forming elite residential parts of the city. With a transition from a semi-rural to a semi-urban context, accompanied by the disappearance of the term summer residence and the introduction of the terms villa and (family) house, the stylistic transition from historicism to functionalism and modern architecture is evident. Three main historical-stylistic periods have been recognized and all the researched buildings have been classified accordingly.